2013
DOI: 10.4103/1658-354x.121079
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided rectus sheath block in children with umbilical hernia: Case series

Abstract: Background:Umbilical hernia repair, a common day-case surgery procedure in children, is associated with a significant postoperative pain. The most popular peripheral nerve blocks used in umbilical hernia repair are rectus sheath infiltration and caudal block. The rectus sheath block may offer improved pain relief following umbilical hernia repair with no undesired effects such as lower limb motor weakness or urinary retention seen with caudal block which might delay discharge from the hospital. Ultrasound guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…There were 23 and 13 articles reporting quality and outcomes of ultrasound imaging for the pediatric population in peripheral and neuraxial blockade, respectively ( Table 2). From the peripheral nerve block (PNB) set, there were 10 RCTs, 4-13 6 prospective observational studies, [14][15][16][17][18][19] 2 retrospective studies, 20,21 and 5 case series [22][23][24][25][26] (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were 23 and 13 articles reporting quality and outcomes of ultrasound imaging for the pediatric population in peripheral and neuraxial blockade, respectively ( Table 2). From the peripheral nerve block (PNB) set, there were 10 RCTs, 4-13 6 prospective observational studies, [14][15][16][17][18][19] 2 retrospective studies, 20,21 and 5 case series [22][23][24][25][26] (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…A case series of children receiving rectus sheath block for umbilical hernia repair also supports a limited need for postoperative opioid consumption-only one of the 22 children required morphine in the postanesthesia care unit (PACU). 26 Multiple RCTs comparing the use of ultrasound-guided PNBs with local anesthetic wound infiltration reported decreased postoperative analgesic consumption after hernia repair in those who received an ultrasound-guided block. 12,13 One of these RCTs reported that children receiving an ultrasound-guided bilateral rectus sheath block for umbilical hernia repair required fewer doses of both opioid and nonopioid medications in PACU when compared with local anesthetic infiltration as a pain control measure.…”
Section: Peripheral Nerve Blocksmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been widely studied in umbilical hernia repair where data from case series indicate that it provides effective analgesia 36,167,177 and may even be used for primary surgical anesthesia [178][179][180] in selected adult patients. However, it is controversial as to whether it offers significant analgesic benefit over simple surgical wound infiltration.…”
Section: Clinical Efficacy Of the Rectus Sheath Blockmentioning
confidence: 99%